Gait Analysis and Fall Risk Assessment in Different Age Groups: A Comparative Study - Thanaporn Sukpramote; Wongwit Senavongse (Engineering Proceedings, 2024)
Daily walking reflects the quality of life concerning physical status and its association with the risk of falls. Abnormal walking can lead to injuries and increase the likelihood of future falls. It has been found that older adults are more prone to falls than younger persons. However, there is limited research on gait analysis in older adults. Thus, we analyzed gait parameters, involving 10 participants aged between 20 and 30 years old, and 10 participants aged 50 years and older, using the Gait Analysis System (LONGGOOD Meditech Ltd., Taipei, Taiwan), which automatically positions the human body and GaitBEST. GaitBEST is used for analyzing and calculating key timing points and displacement values from the Kinect detector as it captures the location of joint points and adjusts them to the program. After the gait testing, the result is displayed immediately. Each volunteer did not have any surgery that impacted their walking and signed a written informed consent statement before the study. The volunteers walked on a straight flat surface for 4.2 m, repeating the walking test five times at a self-determined comfortable speed. Subsequently, a comparative analysis of the gait parameter outcomes was performed using a parametric test by a t-test. The results showed the balance parameters of both groups significantly differed in the head sway range (p = 0.008), head tilt range (p = 0.018), and pelvis tilt range (p = 0.003). The younger group exhibited better postural control than the other group. The spatiotemporal parameters, stride length, and step length during walking were also significantly different at p = 0.001. This indicated that the older group had shorter lengths compared to the other group, leading to a significant difference in the percentage of falls and functional loss at p = 0.021 and 0.023, respectively. The result of this study assists in examining and assessing the physical condition, preventing falls, optimizing walking efficiency, preventing injuries, and reducing the falling risk.